Particulate air pollution and cardiovascular disease mortality in Jiangsu Province, China: a time-series analysis between 2015 and 2021 - Zhu, Fangyu; Yu, Hao; Fan, Xikang; Ding, Zhen; Wang, Qingqing; Zhou, Jinyi (Frontiers in Public Health, 2023)
Introduction: Previous time-series studies have revealed a positive association between particulate matter (PM) and acute cardiovascular effects. However, the evidence mostly comes from developed countries and regions, while the majority of air-pollution-related deaths occur in developing countries. To assess the effect of short-term exposure to PM on daily cause-specific cardiovascular disease (CVD) mortality in Jiangsu Province, China, we investigated 1,417,773 CVD deaths from 2015 to 2021 in Jiangsu.The city-specific association was estimated using generalized additive models with quasi-Poisson regression, and then, random effects meta-analysis was performed to estimate the pooled provincial-average association between acute exposure to PM2.5 and PM10 and cardiovascular disease mortality. To test the independence of PM from gaseous pollutants, we fitted two-pollutant models. Mortality data were also stratified by sex, age, and region to investigate the modification of associations. The exposure-response (E-R) curve from each city was combined using meta-analysis to drive the provincial-level E-R curve.The results showed that each 10-μg/m 3 increase in the PM2.5 concentration was associated with a 0.723% (95% confidence interval (CI): 0.512, 0.935) increase in daily total CVD mortality, a 0.669% (95% CI: 0.461, 0.878) increase in CHD mortality, a 0.758% (95% CI: 0.584, 0.931) increase in stroke mortality, a 0.512% (95% CI: 0.245,0.780) increase in ICH mortality, and a 0.876% (95% CI: 0.637,1.116) increase in CI mortality. The corresponding increases in daily mortality rates for the same increase in the PM10 concentration were 0.424% (95% CI: 0.293, 0.556), 0.415% (95% CI: 0.228, 0.602), 0.444% (95% CI: 0.330, 0.559), 0.276% (95% CI: 0.026, 0.526), and 0.510% (95% CI: 0.353, 0.667), respectively. The association between PM and total CVD mortality remained significant after adjusting for gaseous pollutants. Females, elderly individuals, and districts with lower average PM levels are more sensitive, especially for PM10. The E-R curve for PM on CVD mortality is steeper at lower concentrations and flattens out at higher concentrations.The estimates remained generally consistent in sensitivity analyses when excluding the data during the COVID-19 pandemic period.Discussion: Our time-series study provides evidence of positive associations between acute exposure to PM2.5 and PM10 and total and cause-specific cardiovascular disease mortality in developing countries.